Chemical complexity induced local structural distortion in NiCoFeMnCr high-entropy alloy. Issue 8 (3rd August 2018) - Zhang, Fuxiang; Tong, Yang; Jin, Ke; Bei, Hongbin; Weber, William J.; Huq, Ashfia; Lanzirotti, Antonio; Newville, Matt; Pagan, Darren C.; Ko, J. Y. P.; Zhang, Yanwen
ABSTRACT: In order to study chemical complexity-induced lattice distortion in high-entropy alloys, the static Debye–Waller (D-W) factor of NiCoFeMnCr solid solution alloy is measured with low temperature neutron diffraction, ambient X-ray diffraction, and total scattering methods. The static atomic displacement parameter of the multi-element component alloy at 0 K is 0.035–0.041 Å, which is obvious larger than that of element Ni (∼ 0 Å). The atomic pair distance between individual atoms in the alloy investigated with extended X-ray absorption fine structure (EXAFS) measurements indicates that Mn has a slightly larger bond distance (∼0.4%) with neighbor atoms than that of others. GRAPHICAL ABSTRACT: IMPACT STATEMENT: The chemical complexity induced local structural disorder in the high entropy alloy is distinguished from the thermal contribution by the combination of neutron and X-ray techniques.